2010
DOI: 10.1159/000280763
|View full text |Cite
|
Sign up to set email alerts
|

Muscle MRI in Myotonic Dystrophy Type 1 with Foot Drop

Abstract: The purpose of this study was to investigate the relationship of muscle MRI findings and gait disturbance in myotonic dystrophy type 1 (DM1) patients. Thirteen patients with DM1 were evaluated by manual muscle strength test and muscle MRI of the lower limb. All DM1 patients presenting with foot drop showed high intensity signals in the tibialis anterior muscles on T1-weighted imaging (p < 0.001). The patients presenting with gait disturbance showed high intensity signals in the semimembranosus, vastus intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Several studies have demonstrated lower limb muscle involvement in DM1 patients [10][11][12][13]; however, the detailed distribution of upper limb muscle involvement has not been reported previously.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have demonstrated lower limb muscle involvement in DM1 patients [10][11][12][13]; however, the detailed distribution of upper limb muscle involvement has not been reported previously.…”
Section: Discussionmentioning
confidence: 88%
“…Diagnosis of DM1 was based upon clinical features, family history, genetic studies, electromyography, and muscle biopsy. The patients who had not undergone genetic analysis had typical clinical features of DM1 and a family history of genetically confirmed DM1 (patients 16,19), a family history of congenital DM1 in her sons (patient 17), or typical histology of DM1 in the muscle [2] and family history of typical DM1 in his son (patient 8).…”
Section: Patientsmentioning
confidence: 99%
“…Myotonic discharge was observed in all 17 of the patients examined. The biceps brachii muscle was biopsied in patients 2, 3, 5, and 8 as previously described [2] . Biopsied sections were immediately frozen and thin sections were stained by hematoxylin-eosin and Gomori trichrome.…”
Section: Genetic Studymentioning
confidence: 99%
See 2 more Smart Citations